Outcomes for the treatment of locoregional recurrent nasopharyngeal cancer: Systematic review and pooled analysis. Issue 12 (17th August 2021) - Newton, Ethan; Valenzuela, Dianne; Foley, Joshua; Thamboo, Andrew; Prisman, Eitan
Abstract: Despite advances in the treatment of primary nasopharyngeal carcinoma, locoregional recurrence (lrNPC) occurs at 10%–50% at 5 years. This review aims to evaluate salvage treatment for locally recurrent nasopharyngeal cancer. A literature search for all original articles published on the treatment of lrNPC from January 1990 to January 2021 was conducted. Pooled analysis was performed using a random effects model and assessed statistical heterogeneity of the combined results with I 2 index. Overall, 66 studies were included for analysis. A total of 5286 patients treated with intensity‐modulated radiation therapy (39%), conformal radiotherapy (31%), open nasopharyngectomy (12%), endoscopic nasopharyngectomy (10%), stereotactic radiosurgery (4%), and brachytherapy (4%) were included. Surgical therapy has similar overall survival outcomes to re‐irradiation but with decreased treatment‐related morbidity and mortality. Both surgical and re‐irradiation for lrNPC have similar long‐term survival. Surgical approaches to lrNPC may offer similar survival while avoiding treatment‐associated morbidity and mortality.